Electricity Consumption and Human Capital Development in Nigeria: Exploring the Implications for Economic Growth - Matthew, Oluwatoyin A.; Ede, Christian U.; Osabohien, Romanus; Ejemeyovwi, Jeremiah; Fasina, Fagbeminiyi F.; Akinpelumi, Doris (International Journal of Energy Economics and Policy, 2018)
This study examined the multiplier effect of human capital development through the usage of electricity power for maximum productivity to enhance economic growth in Nigeria. The study engaged data sourced from the World Development Indicators (WDI) for the period 1981-2016, and the Fully Modified Ordinary Least Squares (FMOLS) econometric method was engaged for the analysis. Results from the study showed that, human capital development is insignificantly related to the economic growth in Nigeria, while electricity consumption is significantly linked with economic growth. Therefore, the study recommended that there is a need for the government to develop human capital via the improvement of the educational and health facilities in the country as well as provide electricity in the rural and urban areas for maximum productivity. Keywords: Human Capital, Electricity Consumption, Economic Growth. JEL Classifications: F63, I15; I25; L94 https://doi.org/10.32479/ijeep.6758